A Composite of the Effects of Major Sudden Stratospheric Warming Events on Carbon Dioxide Radiative Cooling in the Mesosphere‐Lower‐Thermosphere - Kumar, Akash; Sunil Krishna, M. V.; Ranjan, Alok K. (Journal of geophysical research. Space physics, 2025)
The major sudden stratospheric warming (SSW) events strongly influence the mean structure of the entire atmosphere, from the troposphere to the thermosphere. These events disrupt the compositional and thermal structure of the mesosphere and lower thermosphere (MLT), causing spatiotemporal variations in the concentration of trace species of this region. Currently, the role of dynamical changes during SSW events on radiative cooling in the MLT region is not well understood. An investigation of the SSW‐induced changes in carbon dioxide (CO2 ${\text{CO}}_{2}$) radiative cooling in the MLT region is presented by examining the changes in the dynamics and transport of key species, such as CO2 ${\text{CO}}_{2}$ and atomic oxygen (O). A composite analysis has been performed to understand these changes during the major SSW events that occurred between 2005 and 2020. The variation of trace species is found to be associated with the change in vertical residual circulation. The results also show that CO2 ${\text{CO}}_{2}$ radiative cooling decreases during the mesospheric cooling that occurs during the stratospheric warming over the polar region. During the recovery stage of the SSW event, the CO2 ${\text{CO}}_{2}$ radiative cooling enhances in the mesosphere. These variations in CO2 ${\text{CO}}_{2}$ radiative cooling are mainly caused by temperature perturbations and oxygen transport in the MLT region. The contribution of temperature change and transport have also been investigated in detail. Plain Language Summary Sudden Stratospheric Warming is a dynamic event that can cause large‐scale changes in stratospheric temperature and polar stratospheric and mesospheric circulation pattern. These changes have been observed to be responsible for many physical and chemical processes in the atmosphere starting from the troposphere up to the thermosphere. Carbon dioxide (CO2 ${CO}_{2}$) is an important trace species responsible for the radiative cooling of the mesosphere and lower thermosphere region. A composite analysis of changes in CO2 ${\text{CO}}_{2}$ radiative cooling during major SSW events that occurred between 2005 and 2020 is presented in this work. It has been found that the radiative cooling decreases during the sudden stratospheric warming (SSW) event over the polar region and its magnitude increases during the recovery of the SSW event. The SSW induced perturbations in temperature and oxygen density have been found to be responsible for the observed changes in radiative cooling intensities. Key Points A composite of major sudden stratospheric warming (SSW) events, and their impact on carbon dioxide (CO2 ${\text{CO}}_{2}$) radiative cooling is studied CO2 ${\text{CO}}_{2}$ radiative cooling decreases and enhances during and after the SSW events Changes in oxygen density and temperature during SSW events primarily influence the CO2 ${\text{CO}}_{2}$ radiative cooling in the mesosphere and lower thermosphere region